Community Perception of the Operational Continuity of Bekotok Landfill in Loa Ipuh, Tenggarong District, Kutai Kartanegara - Anida Shoufhia; Rosmini; Sri Wahyuningsih; Ndan Imang; Henny Pagoray; Yunianto Setiawan (Politeknik Pertanian Negeri Samarinda, 2026)
The increasing volume of waste alongside the expansion of residential areas surrounding landfill sites has become a growing environmental and public health concern. This study aims to analyze community perceptions and the factors influencing public acceptance of the operational continuity of Bekotok Landfil, located in Loa Ipuh Village, Tenggarong District, Kutai Kartanegara Regency. A quantitative descriptive-explanatory approach was employed, involving 70 respondents compirising 61 community members, 3 academics, and 6 local goverment officials, selected through purposivee sampling. Data were collected through questionnaires, interviews, field observation, and documentation, then analyzed using descriptive statistics, Pearson correlation, and Chi-square test. Results indicate that the majority of respondents (57.4%) reported being disturbed by TPA operations, with odor nuisance and reduced environmental comfort as the primary complaints (88.5%). Despite these negative perceptions, 91.8% of respondents supported the continued operation of the Bekotok Landfill, reflecting a pattern of utilitarian acceptance. Length of residence showed a moderate positive correlation with odor disturbance (r = 0.465), while education level was significantly associated with operational support (p = 0.0048). Community expectations centered on odor reduction (88.5%), improved recycling systems (85.2%, and better waste management practices (82%). These findings suggest that the sustainability of Bekotok Landfill depends not only on technical improvement but also on strengthened public communication and environmental management quality.